∫ ( x 4 + 2 x 2 + 3 ) 1 1 x 3 + x d x
The indefinite integral above can be expressed as
g ( a x d + b x e + c ) f + C ,
where a , b , c , d , e , f , g are all integer constants, where d > e , and C represents the arbitrary constant of integration .
Find a + b − c + d − e + f − g .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
there may be better ways to do this but right now I now only of the u substitution way so I came up with this solution.
Let u = ( x + 1 )
notice ( x 4 + 2 x 2 + 3 ) 1 1 can be written as ( ( x + 1 ) 2 + 2 ) 1 1 .
also x 3 + x can also be written as x ( x 2 + 1 ) .
also d u = d x so the integral can be written as u / ( u + 2 ) 1 1 ∗ 1 / 2 ∗ d u .we take the 1 / 2 out of the integral sign (constant).
now we again substitute u 2 = v . also d v = 2 u d u .
again the indefinite integral becomes 1 / 4 (integral sign) ( v + 2 ) − 1 1 d v which is easy to evaluate and we get
( v + 2 ) − 1 0 / − 1 0 + C 1
now we back substitute u and x to get,
( x 4 + 2 x 2 + 3 ) − 1 0 / − 4 0 + C 1
compare co efficients and get the answer.
@Jaydee Lucero done :-) !
How does u = x + 1 imply d u = 2 x d x ?
@Ankit Kumar Jain sorry it is meant to be x dx I have modified it.
@Ankit Kumar Jain was in a hurry so did the double mistakes.
@Ankit Kumar Jain just to make up for my mistakes I offer to you this nice maxima problem check it out https://brilliant.org/problems/maxi-mini-ma/
@Ayon Ghosh just a suggestion: perhaps you can change the variable for arbitrary constant of integration to C 1 so as to avoid confusion with the C inside the parentheses. :)
It's a simple question why make it long.
Problem Loading...
Note Loading...
Set Loading...
I = ∫ ( x 4 + 2 x 2 + 3 ) 1 1 x 3 + x d x = ∫ 4 u 1 1 d u = − 4 0 u 1 0 1 + C = − 4 0 ( x 4 + 2 x 2 + 3 ) 1 0 1 + C Let u = x 4 + 2 x 2 + 3 , d u = 4 x 3 + 4 x d x
⟹ a + b − c + d − e + f − g = 1 + 2 − 3 + 4 − 2 − 1 0 + 4 0 = 3 2